2012
DOI: 10.1039/c1sm06576a
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of two-dimensional systems of dipole-like colloids

Abstract: Based on Discontinuous Molecular Dynamics (DMD) simulations we present a phase diagram of twodimensional nano-particles with dipole-like short-ranged interactions. Similar to systems with true, long-ranged dipolar interactions the present system undergoes a transition from an isotropic fluid phase into a polymer-like fluid, characterized by an association of most particles into clusters. Further decrease of the temperature leads to a percolated system which, moreover, displays dynamical properties reminiscent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 63 publications
4
53
0
Order By: Relevance
“…These building blocks, anisotropic in both shape and chemical constituents, enable one to test some of the classical predictions from extensive theory and simulation [11][12][13][14][15][16][17][18][19] , although to do so is not the main point of this study. The microscopic size of our rods allows direct visualization of dynamic pathways of the resulting dipolar rings in response to external fields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These building blocks, anisotropic in both shape and chemical constituents, enable one to test some of the classical predictions from extensive theory and simulation [11][12][13][14][15][16][17][18][19] , although to do so is not the main point of this study. The microscopic size of our rods allows direct visualization of dynamic pathways of the resulting dipolar rings in response to external fields.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments lag behind extensive theory and simulation of dipolar assembly, even for spheres [11][12][13][14][15][16][17][18][19] . On the experimental side, structures of ferromagnetic nanoparticles were inspected by cryogenic electron microscopy 20,21 , but all dynamics were missing owing to the sample preparation.…”
mentioning
confidence: 99%
“…We consider two particles to be associated into the same cluster if the distance between the spheres is smaller that the critical radius, R c . 15 This critical radius is set to R c ¼ 1.25s (for a similar choice, see ref. 32).…”
Section: Percolationmentioning
confidence: 99%
“…We obtain this time-dependent function by MC simulations, making use of a recently established connection 32 between MC and (overdamped) Brownian Dynamics simulations. 16 To evaluate c BL (t), we assign a variable n ij (t) to each pair of particles, which is 1 if the particles i and j are bonded 15 and zero if not. The bond correlation function is then dened as c BL (t) ¼ hn ij (t)n ij (0)i, averaged over all pairs ij.…”
Section: Persistence Of the Network And Translational Dynamicsmentioning
confidence: 99%
“…29 Schmidle et al performed simulations of two dimensional systems of dipolar spheres in the presence of electric fields and found close agreement between the structures formed in simulation and the experimentally observed structure formed by similar particles. 30,31 Goyal et al showed using discontinuous molecular dynamics (DMD) simulations that three-dimensional systems of spherical dipolar colloidal particles 32 form a number of phases including low volume fraction gels and high volume fraction hexagonally-close-packed, body centered tetragonal and facecentered cubic phases. Additionally, they found that mixtures of these particles formed bicontinuous gels.…”
Section: Introductionmentioning
confidence: 99%